2012
DOI: 10.1007/s00134-012-2530-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrical velocimetry as a tool for measuring cardiac output in small infants after heart surgery

Abstract: EV and Doppler-TTE are interchangeable for estimating SV. EV has the advantages of easy handling and allows continuous measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 26 publications
2
51
0
2
Order By: Relevance
“…An impedance change occurs between diastole and systole as red blood cell orientation is altered from random during diastole to aligned during systole. [1][2][3][4][5][6][7] This device is validated against Fick cardiac output and transthoracic echocardiography in infants and children, 1,2 as well as thermodilation in adults 7 with R values of 0.9. This device is approved by the Food and Drug Administration (FDA) for use in neonates.…”
Section: Methodsmentioning
confidence: 99%
“…An impedance change occurs between diastole and systole as red blood cell orientation is altered from random during diastole to aligned during systole. [1][2][3][4][5][6][7] This device is validated against Fick cardiac output and transthoracic echocardiography in infants and children, 1,2 as well as thermodilation in adults 7 with R values of 0.9. This device is approved by the Food and Drug Administration (FDA) for use in neonates.…”
Section: Methodsmentioning
confidence: 99%
“…The issue of influencing factors or sources of error using EV has been addressed in some adult [30,40] and pediatric studies [8,35,36]. Further, some adult [42] and pediatric studies have assessed the trending ability of the EV method [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 97%
“…Most previous validation studies on EV (and other impedance cardiography devices) compared with different invasive and non-invasive CO monitoring methods have focused on equivalence between methods. These equivalence studies found conflicting data depending on the studied patient group, with better equivalence in more homogeneous or anesthetized patient cohorts [8,10,30,[32][33][34][35] and nonequivalence in inhomogeneous patient groups, with e.g., different cardiac anatomy [36][37][38] or inhomogeneous body fluid composition [39], and an influence of sex, height, increasing CO, and stroke volume [40]. A methodical issue in any CO monitoring method comparison involves the duration of sampling interval time, with better equivalence in validation studies using longer sampling intervals (i.e., more heart cycles) compared to studies using short sampling intervals [41].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…By using transthoracic Echo, the accuracy of EC in term [6,7] and even preterm neonates [8,9,10,11] has been described. It has been studied in different clinical scenarios including surgical ligation for patent ductus arteriosus (PDA) [12], hemodynamic transition after birth [13], caffeine administration [14], and umbilical cord milking in preterm infants [15].…”
Section: Introductionmentioning
confidence: 99%